The microstructure, tensile and impact properties of low-activation ferritic-martensitic steel EK-181 after high-temperature thermomechanical treatment - Polekhina, Nadezhda A.; Linnik, Valeria V.; Litovchenko, Igor Yu; Almaeva, Kseniya V.; Akkuzin, Sergey A.; Moskvichev, Evgeny N.; Chernov, Vyacheslav M.; Leontyeva-Smirnova, Mariya V.; Degtyarev, Nikolay A.; Moroz, Kirill A. (Metals)
In this work, we study the effect of high-temperature thermomechanical treatment (HTMT) with deformation in the austenite region on the microstructure, tensile properties, impact toughness, and fracture features of advanced low-activation 12% chromium ferritic-martensitic reactor steel EK-181. HTMT more significantly modifies the steel structural-phase state than the traditional heat treatment (THT). As a result of HTMT, the hierarchically organized structure of steel is refined. The forming grains and subgrains are elongated in the rolling direction and flattened in the rolling plane (so-called pancake structure) and have a high density of dislocations pinned by stable nanosized particles of the MX type. This microstructure provides a simultaneous increase, relative to THT, in the yield strength and impact toughness of steel EK-181 and does not practically change its ductile-brittle transition temperature. The most important reasons for the increase in impact toughness are a decrease in the effective grain size of steel (martensite blocks and ferrite grains) and the appearance of a crack-arrester type delamination perpendicular to the main crack propagation direction. This causes branching of the main crack and an increase in the absorbed impact energy.